The Estimation risk and its impact in building the optimal portfolio of stock market model framework: Analytical study in the Iraq Stock Exchange - Maitham Rabie Hadi; Zainab Shallal Eakaar (Iraqi Journal for Administrative Sciences, 2024)
This study aimed to build shares portfolios under the traditional approach , which can not take considered Estimation risk and The Bayes approach which takes into consideration Estimation risk And within two cases allow and not allow short-selling and stand out on fundamental differences In construction mechanism and the amount and type of the securities that go into the portfolio, which are excluded from the portfolio. As well as Discuss the impact Estimation risk in building the optimal portfolio of shares in terms of the number of securities that enter the portfolio and in terms trade-off between return and risk namely of the terms of the portfolio performance built. The study was based on the dilemma of two new cases centered the first case about the extent of the portfolio optimization built under the Simplistic models Forum Actions Single indicator model is particularly and The feasibility of and simplicity brought by comparison with the base model of Markowitz . The second controversial case is represented the extent of the effect of Estimation risk in the performance of optimal the portfolio based on Assume of default allow and not allowed to sell short compared to the optimal the portfolio Which it be a corresponding, which was built under the simple staging model based to market index model The study sample consisted of companies listed on the Iraq Stock Exchange, amounting to (42) companies belonging to various economic sectors for a period of 60 months, from October 2010 until October 2015. On the basis of many models and The financial and The statistical methods , The study concluded many of the the conclusions, perhaps the most important that the Estimation risk and a clear impact in building the optimal the portfolio according to Bayes approach when compared with the traditional approach and This reflects the influence additives risk of a optimal portfolio Because of parametric uncertainty and this is achieved according of two cases allow and not allow short-selling . This effect taking the way to the performance of the built portfolio , if it appears that the built portfolio performance of according of the Bayes approach superiority on the wallet peer built performance of according of traditional approach, which does not take into account the Estimation risk , especially in the case not to allow short selling demand is the most important condition for investors dealers in Iraq market Securities So The study comes out with many recommendations perhaps the most important the need to to give the utmost attention by the participants in the Iraq Stock Exchange In Bayes approach which translates the effect of Estimation risk in the performance of optimal the portfolio built compared with the traditional simplistic approach Which is Simplified approach from the side And accurately On the other in building the optimal the portfolio compared with the Markowitz approach basis on which experience from complicated calculation and implementation